Cognitive Retardation in a Patient with Preservation of Psychomotor Speed - J. R. Willison; E. K. Warrington (Behavioural Neurology)
We describe a patient (R.S.) who after a bout of probable TB exhibited an unusual pattern of response retardation, although given time he was able to score at a satisfactory level. He was strikingly slow to initiate speaking and to carry out higher level cognitive tasks, at a time when he could complete a variety of psychomotor activities at normal speed. He showed many similarities with patients previously described as having subcortical dementia. The selective preservation of psychomotor responding in the context of his gross bradyphrenia, however, was unexpected.